SAPUT POLENG DALAM PENCIPTAAN KARYA SENI LUKIS DENGAN TEKNIK OPAQUE DAN IMPASTO - Suyasa, I Nyoman; Rahman, Deni (Acintya, 2017)
The research titled â€œSaput Poleng dalam Penciptaan Karya Seni Lukis dengan Teknik Opaque danImpastoâ€ was an art creation research based on the development of painting that served as an awareness media of nature conservation by raising local wisdom as symbol of natural balance. Polengcloth was a symbol of natural balance. In everyday life, Hindus in Bali, especially in Hindu ritualactivities, often wore objects or woven fabrics with various colors, such as white, red, yellow, or amixture of these colors. The variety of colors used was not just for enhancing the beauty of theceremonies in order to make them look splendid, but actually the use of color was based on thephilosophical meaning derived from the Vedic scriptures. This research used several methods of artistic research (art creation). These stages included: research, experimentation, contemplation, and formation. The research was focused on the meaning of poleng cloth in nature conservation, usingmetaphor language in its disclosure, visualizing it by combining opaque technique and impasto technique. These technique was used to create cloth characters and tree characters. Utilized acrylic paintas the ingredient, because in addition to dry quickly, this paint brought unexpected effects added tothe artistic value. The hope was, by creating this painting in addition to experimenting and exploringfor new possibilities in combining opaque techniques with wider and free impasto techniques, thepainting was also became awareness media to be more concerned with nature conservation.Keywords: Saput poleng, metaphor, opaque and impasto.